LIMING AND FERTILIZATION WHEN GROWING MELON - Santos Zebalos, Carlos Henrique dos; Soares, Edimar Rodrigues; Barbosa, Camila de Lira; Nogueira, Adriana Ema; Queiroz, Samira Furtado de [UNESP] (Faema-fac Educacao & Meio Ambiente, 2017)
In the last decades, Brazil has earned its place on the spotlight because of the production and sale of melon. The growth is concentrated in the northeast region, and the fruit is sold worldwide. The melon is a typical culture from warm climates and may also be cultivated in the north region, especially in the state of Rondonia. Deploying such culture may represent a new source of income to small and medium producers, contributing to the sustainability of agricultural properties. Literature lacks data about melon chemical necessities, with no information about fertilization or liming, which directly affects the productivity and quality of the plants and their fruits. This study aims to present data concerning the nutritional demand of the melon, as well as chemical aspects of the soil that favor its development. In terms of liming, the recommendation is to elevate base saturation to 80%. However, there is no evidence in previous literature about limestone deployment in such culture. It has been verified that, generally, potassium is the most drawn component by this culture. Doses of 80 kg ha(-1) of nitrogen seem to be sufficient to obtain good productivity. There are few researches based on phosphorus and potassium. Research has indicated that 274 kg ha(-1) of P2O5 are enough to cause maximum productivity of the culture. However, more study is needed to reach further conclusion about these two nutrients.
Keywords: Cucumis melo L.; Nutrition; Fertilizers; Productivity